Silver nanoparticles for the inhibition of Staphylococcus aureus - Miguel Ángel Ortiz-Gila; Rosa Elvira Nuñez-Anita; Ma. Concepción Arenas-Arrocena; Omar Martínez-Álvarez; Joel Emiliano-Ramírez; Javier de la Fuente-Hernández; Laura Susana Acosta-Torres (Entreciencias: Diálogos en la Sociedad del Conocimiento)
A large microbial ecosystem exists in the oral cavity where Staphylococcus aureus (S. aureus) can be found, causing oral pathologies such as angular cheilitis, mumps and staphylococcal mucositis. This pathogenicity is due to the virulence factors, toxins and multi-resistance to antibiotics in the oral cavity, which contributes to its colonization. Microbial colonization in the oral cavity by S. aureus has been isolated from healthy patients in a range of 24% to 36%. However, the incidence has increased to 48% in patients with dentures due to the formation of biofilm on the surface of the dentures. Currently, there is no treatment for oral infectious without the use of antibiotics. Recent investigations indicate that silver nanoparticles (AgNPs) are a promising material or strategy to eliminate S. aureus because of their well-known antibacterial effect. However, the mechanism of the inhibitory effect of Ag ions on S. aureus is only partially known and very little has been reported. Therefore, the purpose of the present systematic review is to determine the strategies and challenges of the use of antimicrobial biomaterials with AgNPs versus oral S. aureus infections.